2023
DOI: 10.1007/s10120-023-01437-7
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine modification of OIP5-AS1 promotes glycolysis, tumorigenesis, and metastasis of gastric cancer by inhibiting Trim21-mediated hnRNPA1 ubiquitination and degradation

Rongjun Xie,
Longfei Liu,
Xianzhou Lu
et al.

Abstract: Background Opa-interacting protein 5 antisense transcript 1 (OIP5-AS1) has been demonstrated to play vital roles in development and progression of tumors such as gastric cancer (GC). However, the detailed molecular mechanism of OIP5-AS1 has not been completely elucidated. Our study aimed to investigate the role and the epigenetic regulation mechanism of OIP5-AS1 in GC. Methods OIP5-AS1 expression in GC tissues was detected by RT-qPCR. Loss- and gain-of-fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Aerobic glycolysis is the primary pathway by which tumor cells utilize glucose, known as the Warburg effect 12 , 13 . Numerous studies have indicated that tumor cells modulate the expression of glycolysis-related proteins through ubiquitin modification, thereby activating or inhibiting the glycolytic pathway 14 , 15 , 16 . For instance, the E3 ligase Fbw7 inhibits glycolysis in diffuse large B-cell lymphoma by promoting the ubiquitin-mediated degradation of LDHA 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerobic glycolysis is the primary pathway by which tumor cells utilize glucose, known as the Warburg effect 12 , 13 . Numerous studies have indicated that tumor cells modulate the expression of glycolysis-related proteins through ubiquitin modification, thereby activating or inhibiting the glycolytic pathway 14 , 15 , 16 . For instance, the E3 ligase Fbw7 inhibits glycolysis in diffuse large B-cell lymphoma by promoting the ubiquitin-mediated degradation of LDHA 14 .…”
Section: Introductionmentioning
confidence: 99%
“…HectH9, through K63-linked ubiquitination, facilitates the transfer of HK2 to mitochondria and enhances glycolysis in prostate cancer 15 . Moreover, TRIM21, by means of ubiquitinating hnRNPA1 and thereby inducing degradation, curtails aerobic glycolysis in gastric cancer cells 16 . However, further investigation is needed to determine whether TRIM50 can modulate glycolysis in GC cells through its function as a ubiquitin ligase.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, m6A modification participates in the various aspects of tumor development, such as immunity, metabolism, and tumor stem cells’ self-renewal[ 18 , 19 ], emerging as an important molecular biomarker in tumor initiation and development. m6A dysregulation exerts multiple regulatory effects in GC[ 20 , 21 ]. The pathogenic mechanism of H. pylori as a significant risk factor for GC remains unclear.…”
Section: Introductionmentioning
confidence: 99%